POST-LAPAROSCOPIC SHOULDER PAIN: A NARRATIVE REVIEW OF A FREQUENT POSTOPERATIVE SEQUELA - Salati, Sajad Ahmad; AlSuwaydani, Saleh (Sanamed, 2026)
While the adoption of laparoscopic surgery has enhanced patient safety, comfort, and satisfaction, a considerable number of patients experience post-laparoscopic shoulder pain (PLSP), which can slow recovery. The English-language literature was reviewed after searching major academic databases and engines, including PubMed, Google Scholar, ResearchGate, and Web of Science, to summarize the current understanding of the etiopathogenesis, associated risk factors, and management strategies for post-laparoscopic shoulder pain. The precise etiology remains undefined, and several theories have been proposed to explain PLSP. The most widely accepted theory suggests that PLSP is a form of referred pain caused by diaphragmatic irritation due to stretching from pneumoperitoneum or the presence of residual gases and fluids. Currently, there are no universally accepted protocols for either the prevention or treatment of PLSP; consequently, a wide range of modalities are applied based on the surgeon’s expertise and preference. There is a clear need to improve awareness of this condition to enable the standardization of management options, thereby optimizing patient outcomes.
Keywords: Laparoscopic Surgery; Shoulder pain; Referred pain; Pneumoperitoneum; Carbon dioxide; Diaphragm; Phrenic nerve